Low power, low voltage on chip relaxation oscillator. Issue 4 (1st October 2016) - Wadhwa, Sanjay Kumar; Sinha, Anand Kumar
ABSTRACT: A low power, low voltage resistor-capacitor or relaxation oscillator circuit is proposed. The proposed relaxation oscillator works with minimum 1.1  V supply and consumes less than 3  uA average current for 128 KHz output frequency. A novel integrated comparator and bias current reference circuit ensures low current consumption and low silicon area while providing good output frequency stability across voltage and temperature variation. Capacitor trimming is used to tune the output frequency across process variation. The proposed circuit is designed in 40  nm complementary metal oxide semiconductor process and simulation and silicon measurement results are provided to show the functionality.